The Marketing Of Tourism Villages Through Annual Event: Case Study Of Penglipuran Village Festival - Putra, I Nengah Sandi Artha; Arini, Ni Nyoman; Raditya, I Putu Tiana (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2023)
Tourism villages in their development must have a good marketing strategy. Many tourist villages are not developing and progressing because the management and marketing aspects are not carried out properly. The development of a tourist village through an annual event strategy is one of the strategies carried out by independent tourism villages such as the Penglipuran Tourism Village. This study aims to examine the marketing strategy of Penglipuran Tourism Village through an annual event. Two objects that will be studied in the event are event management and marketing strategy. A qualitative approach is the method used in this study. The in-depth interview technique is a technique used to search for data in depth with a purposive sampling technique. The results of this study indicate that there is good event management carried out by the committee which consists of aspects of research, design, planning, coordinating and evaluating. The eight elements of the marketing mix are also applied in the event marketing strategy, such as product, price, place, promotion, people, packaging, programming and partnership aspects. Penglipuran Village Festival as an annual event is managed independently based on the community and is consistently carried out every year. This event has a good impact on the existence of tourism village branding, and provides economic, socio-cultural and environmental welfare benefits.